Prediction of Mental Health in MS Patients: The Role of Psychological Resilience and Cognitive Integration - Kazemi, Maryam (Advances in Nursing & Midwifery, 2019)
Abstract Introduction: Multiple Sclerosis is a chronic disease of the central nervous system in which myelin damage occurs locally. This study was conducted to predict the mental health of patients with MS regarding cognitive integration and psychological resilience. Methods: In a correlational-descriptive study, all people with MS disease in the west of Iran in 2015 were studied. Hundred people were selected from medical and clinical centers by using easy sampling method. They filled out acceptance and action of Bond et al (2011), cognitive incongruity Gillanders et al (2014), mental health (GHQ-12) and Demographic Information Sheet questionnaires. Pearson correlation factor and regression efficiency factor were used to analyze data with SPSS V. 22 software. Results: The results showed that mental health has a negative correlation with psychological integration (r=-0.438, P<0.001) and positive significant correlation with psychological resilience (r=0.487, P<0.001). Regression analysis showed that 24.3% of mental health variance factor is predicted by psychological resilience (P<0.001). Conclusions: According to the results, information and knowledge could be provided by holding training courses to increase psychological resilience, so that mental health of MS patients would be provided.